Pembagian Bidang Penelitian Pendidikan Islam - Risman Yusup; Alda Risca; Firda Malapo; Moh Arif (IAIN Ternate, 2022)
In carrying out Islamic education research in order to get maximum results and the results can be useful for the world of education in order to improve the quality of Islamic education, then of courseresearchers must pay attention to research procedures, types of research, methods used must be appropriate and also relevant research models. Islamic education. The reality in the field today is that we often find educators lazy to conduct research in order toovercome the problems they face in carrying out their daily tasks. Even though it is very important to do considering educators play a very large role in realizing the expected goals of Islamic education. On the other hand, there are also researchers who conduct research but because they do not pay attention to the correct research procedures, in the end the research carried out cannot be held accountable. This is certainly very sad considering the many types of research and research methods that we can choose that we can use for Islamic education research. The basic concept of Islamic education research is basically the same as the basic concept of educational research in general, only the object of study focuses on Islamic education. The purpose of Islamic education researchis to obtain the correct knowledge of Islamic education.